STUDENTS’ PERCEPTION TOWARD GOOD LECTURER PEDAGOGICAL COMPETENCE - Rahman, Ali Wira (Elite : English and Literature Journal, 2016)
As the application of the four competencies for the lecturers in teaching and learning, it becomes a new business for them to fulfill those competencies (pedagogical professional, personality, social). This has an impact on the provision of a new method for students in learning activities so that a teacher would be able to develop a curriculum in accordance with the respective educational unit and the local needs of each student. The first pedagogical competence deals with the ability of a lecturer in managing the classroom and facilitates the students’ diversity. Sometimes lecturers apply different pedagogic actions with students’ perceptions so that what is they supposed good by lecturers sometimes inversely with students’ intake. The aim of this study was to facilitate the perception of the students in regard to the pedagogical action of a good lecturer. The result supposed to be a consideration from the lecturer in applied pedagogical action in the classroom.